Harmonization of Teachers and Students in Improving a Conducive Learning Climate - Nurdalia, Nurdalia (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The learning process involves two main elements, teachers and students, who interrelate and influence each other. Harmonization in their relationship is not only a prerequisite for creating a conducive learning atmosphere but also a foundation for character formation and academic achievement. Therefore, the purpose of this study is to describe how teacher-student harmony creates a conducive learning climate. The type of research used in this study is a literature study. Data collection for literature studies involves searching, reading, and recording information from various written sources such as books, journals, articles, and reports to uncover theoretical foundations, develop a framework for thinking, and acquire knowledge relevant to the research problem. The stages of the research process include determining keywords, searching for literature using search engines or catalogs, selecting relevant sources, and analyzing and organizing the data to draw conclusions that address the problem formulation. The results of the study indicate that harmonization describes a condition of a harmonious, balanced, and mutually supportive relationship. For teachers and students, harmonization means establishing beneficial communication, mutual respect, and a shared understanding in carrying out the learning process. Harmonious relationships create a conducive, empathetic learning climate that optimally develops students' potential. A conducive learning climate is a learning environment, both physical and psychological, that supports effective learning. This environment encompasses social interactions between teachers and students, classroom management, classroom cleanliness and comfort, and students' feelings of safety and respect.